Salience Network Connectivity and Social Processing in Children With Nonverbal Learning Disability or Autism Spectrum Disorder - Margolis, Amy E. (Neuropsychology, 2018)
OBJECTIVE: Nonverbal learning disability (NVLD) is a putative neurodevelopmental disorder characterized by spatial processing deficits as well as social deficits similar to those characteristic of autism spectrum disorder (ASD). Nonetheless, NVLD may be a distinct disorder that is differentially associated with the functioning and connectivity of the salience (SN) and default mode (DMN) networks that support social processing. Thus, we sought to assess and compare connectivity across these networks in children with NVLD, ASD, and typically developing children. METHOD: Resting-state fMRI data were examined in 17 children with NVLD, 17 children with ASD selected from the Autism Brain Imaging Data Exchange (ABIDE), and 40 TD children (20 from ABIDE). Average DMN and SN functional connectivity and pairwise region-to-region connectivity were compared across groups. Associations with social impairment and IQ were assessed. RESULTS: Children with NVLD showed reduced connectivity between SN regions (anterior insula to anterior cingulate and to rostral prefrontal cortex [rPFC]), whereas children with ASD showed greater connectivity between SN regions (supramarginal gyrus to rPFC) relative to the other groups. Both clinical groups showed higher levels of parent-reported social problems, which related to altered SN connectivity in the NVLD group. No differences were detected in overall average connectivity within or between networks. CONCLUSIONS: The social deficits common across children with NVLD and ASD may derive from distinct alterations in connectivity within the SN. Such findings represent the first step toward identifying a neurobiological signature of NVLD.